Potential technique for tiny crystalline detection in lycopene-loaded SLN and NLC development - Okonogi S. (Informa Healthcare, 2014)
Context: The advantage of solid nanocarriers like solid lipid nanoparticles (SLN) or nanostructured lipid carriers (NLC) is related to some degree of crystalline characteristics of the lipid. However, the detection of tiny content of crystalline structure in such nanoparticles is difficult. Objective: The aim of this study was to explore a potential method for detection of low degree of crystalline characteristics of lycopene-loaded SLN and NLC. Methods: Crystalline characteristics investigation was done by polarized light microscope (PLM), differential scanning calorimeter (DSC), X-ray diffractometer (XRD) and transmission electron microscope (TEM). Results and discussion: It was found that high crystalline characteristics as anisotropic molecular organization crystal of pure orange wax and lycopene could be investigated by PLM, DSC and WAXS. Low crystallinity of lycopene-loaded SLN and NLC could not be detected by those techniques. Electron diffraction mode of TEM showed potential detection of tiny crystalline characteristics of such systems. The diffraction pattern of lycopene-loaded SLN and NLC exhibited obvious zero order laue zone indicating an isotropic fine grained polycrystalline of the nanoparticles. Conclusion: It could be concluded that TEM is a promising method for detection of low-level crystallinity of solid nanocarriers. © 2014 Informa Healthcare USA, Inc.